The role of socio‐economic status and energy‐density in Australian women of child‐bearing age. Issue 5 (28th February 2020) - Latter, R.; Brown, L. J.; Rae, K. M.; Rollo, M. E.; Schumacher, T. L.
Abstract: Introduction: An optimal diet is imperative in preparing women for pregnancy and this may be influenced by socio‐economic status (SES). This research aims to investigate the role of SES on the dietary energy density (ED) in Australian women of preconception age. Methods: A secondary analysis of the Australian National Nutrition and Physical Activity Survey 2011–12 for females aged 18–39 years ( n  = 1617) was conducted. Dietary intake was assessed by 24‐hr recalls and dietary ED by dietary energy per weight (kJ.g −1 ). ED was further categorised as ED of foods and beverages separately. SES was assessed by three variables: Socio‐Economic Indexes for Areas (SEIFA), developed by the Australian Bureau of Statistics; income decile; and level of education. Linear mixed model regressions were used to identify associations between ED and SES. Results: The median ED for food, beverages and combined food and beverages was 9.38 kJ g −1, 1.02 kJ g −1 and 7.11 kJ g −1, respectively. No significant variation was explained by SES variables when analysing combined ED in the adjusted model or ED from foods. Income decile reduced ED of beverages, although with little effect (coefficient: −0.04, P  = 0.002). Significant confounders included inactivity, which increased ED in both combined ED and ED foods (coefficient: 0.51, P  = 0.001 and coefficient: 0.78, P  < 0.001). Conclusions: SES explained little variation in dietary ED in women of childbearing age. A large proportion of women had high energy‐dense diets regardless of their SES. These findings suggest that a large proportion of women, who may become pregnant, have diets that exceed the international recommendations for dietary energy density. Abstract : An optimal diet is imperative in preparing women for pregnancy and this may be influenced by socio‐economic status (SES). However, the present study found that a large proportion of Australian women of child‐bearing age had high energy‐dense diets, regardless of their SES.